DEVELOPMENT OF THE BANKING SECTOR OF UKRAINE IN THE SPACE OF FORMATION OF DESTRUCTIVE CONSEQUENCES OF THE INFLUENCE OF THE GLOBAL FINANCIAL AND ECONOMIC CRISES: ECONOMIC AND LEGAL ASPECTS - Vovk Viktoriia Yakivna; Zhezherun Yuliіa Volodymyrivna; Kostohryz Viktoriia Hryhorivna; Maliarova Valeriia Olehivna (Scientific Journal of Pedagogy and Economics, 2021)
The article examines the impact of globalization on the development of the world and national economic systems. The high probability of a global economic recession due to the coronavirus outbreak is projected to have significant consequences for both the global economy and the economy of Ukraine. Due to the probable change in the structure of the world economy and logistics, there is a growing need to study the risks of the national banking system, which demonstrates a high dependence on global financial markets. The peculiarities of the manifestation of financial and economic crises in the conditions of turbulence of the international financial markets and strengthening of financial instability have been considered. The causes and consequences of crises in the banking sector of Ukraine have been studied. The analysis of macroeconomic indicators of economic development of Ukraine during 2006-2019 with identifying of crisis periods has been carried out. Particular attention has been paid to the study of the preconditions for the emergence and consequences of the global financial and economic crisis for the economy of Ukraine in general and the banking sector in particular. Indicators that characterize the degree of penetration of the banking system into the economy of Ukraine have been analyzed, that will determine the features of crises at different stages of socio-economic development and conduct a comparative assessment of anti-crisis measures of the NBU aimed at stabilizing the banking sector. Taking into account the fact that the causes of financial and economic crises are not identical, measures used during the Global Financial and Economic Crisis of 2007-2011 cannot be taken to overcome the negative consequences of the Coronacrisis of 2020. Regulatory aspects of the banking system in times of crisis have been systematized. An attempt to predict the possible development of events in the domestic banking sector in the context of the Coronacrisis of 2020 has been made. The purpose of the article is to study the development trends of the banking sector of Ukraine in the space of formation of the destructive consequences of the global financial and economic crises and to determine the main directions of anti-crisis regulation of banking.